2018
DOI: 10.4081/jae.2018.801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of canopy development in the vineyard on spray deposition from a tunnel sprayer

Abstract: Spray deposition from a tunnel, air-assisted sprayer was analysed during the whole season, following canopy development in a vertical-shoot-positioned vineyard. Four field tests were performed using hollow-cone, turbulence nozzles between the BBCH 15 (5 leaves unfolded) and BBCH 77 (berries beginning to touch) growth stages, plus an additional test with flat-fan, air-injection nozzles at BBCH 77. The main canopy parameters were assessed, including the canopy height range (0.6 m to 1.4 m), the leaf area index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…After a deep evaluation of canopy deposition in vineyards, Perguer and Petris (2008) found that the LWA method could be considered sufficiently accurate in a wide range of vineyards with a foliar area/canopy cross-section in the row direction ratio of lower than four. These results were also matched by Pergher and Zucchiatti (2018).…”
Section: Fundamentals Of Dosaviñasupporting
confidence: 68%
See 1 more Smart Citation
“…After a deep evaluation of canopy deposition in vineyards, Perguer and Petris (2008) found that the LWA method could be considered sufficiently accurate in a wide range of vineyards with a foliar area/canopy cross-section in the row direction ratio of lower than four. These results were also matched by Pergher and Zucchiatti (2018).…”
Section: Fundamentals Of Dosaviñasupporting
confidence: 68%
“…Where: LWA is the leaf wall area in both sides of the crop (m 2 ha -1 ); C h is the canopy height (m); and r is the distance between rows (m) However, the conventional LWA method, even if it is based on the canopy structure, does not consider other important and influencing parameters such as canopy width and leaf density, which both directly affect spray distribution quality. Foliar deposits at different locations across the canopy are directly influenced by canopy characteristics, mainly height and depth (Pergher and Zucchiatti, 2018). Furthermore, spray distribution quality, including losses to the ground and drift, is directly influenced by the type of sprayer.…”
Section: Fundamentals Of Dosaviñamentioning
confidence: 99%
“…For this reason, many treatments use conventional orchard sprayers based on hydraulic systems for droplet production and air assistance for droplet transport and penetration into the canopy. As different vineyards have different training systems, a wide range of sprayers can be adopted, such as mist-blowers (Grella et al, 2017a), multi-row sprayers (Pergher and Zucchiatti, 2018), or individual outlet sprayers (Miranda-Fuentes et al, 2018). These machines atomize spray liquid using pressure nozzles, distributing the droplets on the vegetation using an artificial air current that moves the leaves, helping the droplets penetrate the internal canopy (Fox et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have proven that droplet drift is more severe in axial fan sprayers compared to tower sprayers ( Landers et al., 2017 ). Different types of sprayers have been developed in order to improve the effectiveness of the sprayers, such as multi-airway sprayers ( Grella et al., 2020 ), multi-row sprayers ( Pergher and Zucchiatti, 2018 ), or individual outlet sprayers ( Miranda-Fuentes et al., 2018 ). To reduce pesticide use and improve pesticide deposition on grape leaves, an electrostatic sprayer using an innovative pneumatic electrostatic sprayer was developed ( Simone and Emanuele, 2015 ).…”
Section: Introductionmentioning
confidence: 99%